Catalytic, Enantioselective Sulfenofunctionalization of Alkenes: Development and Recent Advances. Issue 45 (18th August 2020) - Matviitsuk, Anastassia; Panger, Jesse L.; Denmark, Scott E.
Abstract: The last decade has witnessed a burgeoning of new methods for the enantioselective vicinal difunctionalization of alkenes initiated by electrophilic sulfenyl group transfer. The addition of sulfenium ions to alkenes results in the generation of chiral, non‐racemic thiiranium ions. These highly reactive intermediates are susceptible to attack by a myriad of nucleophiles in a stereospecific ring‐opening event to afford anti 1, 2‐sulfenofunctionalized products. The practical application of sulfenium ion transfer has been enabled by advances in the field of Lewis base catalysis. This Review will chronicle the initial discovery and characterization of thiiranium ion intermediates followed by the determination of their configurational stability and the challenges of developing enantioselective variants. Once the framework for the reactivity and stability of thiiranium ions has been established, a critical analysis of pioneering studies will be presented. Finally, a comprehensive discussion of modern synthetic applications will be categorized around the type of nucleophile employed for sulfenofunctionalization. Abstract : Functionalize through thiiranium ions : Sulfenyl group transfer to alkenes has emerged as a versatile tool for introduction of organosulfur moieties into molecules with high stereochemical control. Understanding the structure, formation, stability, and reactivity of the key intermediate thiiraniium ion, led to the development of catalytic enantioselective sulfenofunctionalizations highlighted in this Review.